Integration of canonical and noncanonical Wnt signaling pathways patterns the neuroectoderm along the anterior-posterior axis of sea urchin embryos. - Ryan C Range; Robert C Angerer; Lynne M Angerer (PLoS Biology)
Patterning the neuroectoderm along the anterior-posterior (AP) axis is a critical event in the early development of deuterostome embryos. However, the mechanisms that regulate the specification and patterning of the neuroectoderm are incompletely understood. Remarkably, the anterior neuroectoderm (ANE) of the deuterostome sea urchin embryo expresses many of the same transcription factors and secreted modulators of Wnt signaling, as does the early vertebrate ANE (forebrain/eye field). Moreover, as is the case in vertebrate embryos, confining the ANE to the anterior end of the embryo requires a Wnt/β-catenin-dependent signaling mechanism. Here we use morpholino- or dominant negative-mediated interference to demonstrate that the early sea urchin embryo integrates information not only from Wnt/β-catenin but also from Wnt/Fzl5/8-JNK and Fzl1/2/7-PKC pathways to provide precise spatiotemporal control of neuroectoderm patterning along its AP axis. Together, through the Wnt1 and Wnt8 ligands, they orchestrate a progressive posterior-to-anterior wave of re-specification that restricts the initial, ubiquitous, maternally specified, ANE regulatory state to the most anterior blastomeres. There, the Wnt receptor antagonist, Dkk1, protects this state through a negative feedback mechanism. Because these different Wnt pathways converge on the same cell fate specification process, our data suggest they may function as integrated components of an interactive Wnt signaling network. Our findings provide strong support for the idea that the sea urchin ANE regulatory state and the mechanisms that position and define its borders represent an ancient regulatory patterning system that was present in the common echinoderm/vertebrate ancestor.